(untitled) (Annals of Medical Research, 2021)
Aim: Pilonidal sinus disease is a disease that is commonly seen in surgical practice. So far, many factors have been blamed in the development and etiology of pilonidal sinus disease. Our aim was to investigate whether a particular dressing habit, tucking of the undershirt into underwear, had a role in the development of pilonidal sinus disease. Materials and Methods: Between January 2013 and May 2015, 923 patients with pilonidal sinus disease were admitted to our clinic. These patients and 685 other patients who presented to our clinic with other benign diseases (cholelithiasis etc.) were questioned about their dressing habits.Results: In our study we questioned undershirt tucking habit; 444 (48%) of the patients with pilonidal sinus disease had a habit of tucking their undershirt into their underwear, while 479 (52%) did not. Whereas, in the control group, 384 (56%) had this habit, while 301 (44%) did not. Comparisons revealed a statistically significant difference between patients and controls in terms of undershirt tucking habits; those with pilonidal sinus disease were more likely to not tuck their undershirts into their underwear.Conclusions: This is the first study to show that a simple, costless dressing precaution may be effective in the prevention of pilonidal sinus disease. Further studies with better-organized groups are required to confirm our findings.